2011
DOI: 10.1097/jto.0b013e31820b8891
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Superior Mediastinal Lymph Node Metastases on Prognosis in Non-small Cell Lung Cancer Located in the Right Middle Lobe

Abstract: Superior mediastinal lymph node metastases and #11i metastases were significant adverse prognostic factors in patients with middle lobe lung cancer, and they were associated with each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
4
8
0
Order By: Relevance
“…This is supported by our results that show rare involvement of the interlobar nodes of the middle lobe. Third, the prognostic impact must be different from that for other lobes (9). The findings of our study were consistent with those of other reports, with the prognosis being significantly worse for patients with mediastinal LN metastases than for those with N1 nodes only.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is supported by our results that show rare involvement of the interlobar nodes of the middle lobe. Third, the prognostic impact must be different from that for other lobes (9). The findings of our study were consistent with those of other reports, with the prognosis being significantly worse for patients with mediastinal LN metastases than for those with N1 nodes only.…”
Section: Discussionsupporting
confidence: 91%
“…In this report, the TI for #10 was comparable to that for UZ, but was lower than that for SCZ. Moreover, the incidence of #11s metastases (5.6%) was similar to that reported in a previous study (9). We hypothesized that #11i metastases were retrograde because antegrade drainage to the superior mediastinum from mediastinal metastasis was disturbed.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In general, the characteristics of lung cancer arising from the middle lobe have been described as follows: 1) high frequency of extralobar invasion or pleural dissemination, and 2) numerous lymphatic drainage sites extending to both the superior and inferior mediastinal zones [4][5][6]. First, we demonstrated that the rate of incomplete resection was higher for cancers located in the RML than for those located in the other lobes.…”
Section: Commentmentioning
confidence: 71%